Photolanguage as a Research Tool in Adult and Community Education - Wendy Griswold; La Barbara James Wigfall (Adult Education Research Conference, 2015)
Photolanguage facilitates reflection and discussion in small group settings. It is useful as a research tool as it elicits rich data for analysis. Used in an environmental justice community, the use of Photolanguage provided insight into participants’ motives, involvement in, and vision for a redevelopment project.
Keywords: photolanguage; reflection; environmental justice; community sustainability